PENERAPAN BLUE OCEAN STRATEGY DI PT. X DALAM MENGHADAPI PERSAINGAN PENJUALAN AUTOMATIC TANK GAUGING DI INDONESIA - Nissyia Mazhaly; Dadan Umar Daihani; Parwadi Moengin (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
PT. Bona Metal Packaging is a company that move within area of making alumunium tube. In the current era of globalization oil industry was thriving. Please note this problem in many companies today are focused to compete with each other (Red Ocean Strategy) of differentiation of goods, snatch market share, competitive advantage, and low cost strategy. Red Ocean Strategy is important, but at a certain saturation point of this strategy is no longerprofitable for the company. Therefore, it would be nice to begin to look for the Blue Ocean Strategy that tends away from the competition. The aim is to produce a new business development strategy and has Blue Ocean Strategy in PT.X Indonesia in the period from 2013 to 2014. By analyzing the external and internal analysis, and SWOT analysis will get the results of the Blue Ocean Strategy formulation is seen from the Strategy Canvas, 4 Action Frameworkand ERRC Grid. From the formulation of blue ocean strategy is obtained which is expected to know the alternative is a new strategy Blue Ocean in the oil and gas industry.